Elaboración e implementación de un plan de mantenimiento preventivo en equipos de línea blanca. (2020)
The present project was carried out with the purpose of generating a maintenance guide for a line of White line equipment, especially air conditioning, washing and refrigeration equipment. In order to highlight the timely detection of faults that these appliances may present, and thus mitigate damage or breakdowns in time, which in turn safeguard their useful life and provide optimal operation.